Evidence from West Africa on the interplay of affective behavioral cognitive and ethical dimensions of AI literacy in Ghanaian and Nigerian Universities - Muhammad Zaheer Asghar; Kwasi Agyemang Duah; Javed Iqbal; Hanna Järvenoja (Discover Computing)
Abstract This study addresses the need for context-specific Artificial Intelligence (AI) literacy research in West Africa, confronting challenges such as interrelation of AI literacy dimensions, ethical concerns, and a scarcity of localized studies. It investigates AI literacy among university students in Ghana and Nigeria through a quantitative cross-sectional survey of 427 participants (n = 206 Ghana, n = 221 Nigeria). The investigation focuses on four interconnected dimensions from the ABCE framework: Affective (motivation, self-efficacy), representing emotional engagement with AI; Behavioral (collaboration, intentional use), reflecting active participation in AI-related tasks; Cognitive (knowledge, critical thinking), encompassing understanding and application of AI concepts; and Ethical, pertaining to awareness and commitment to AI's societal implications. Using partial least squares structural equation modeling (PLS-SEM), findings confirm that affective factors positively influence cognitive outcomes, mediated by behavioral engagement and ethical understanding. Notably, country differences do not significantly affect these relationships, thereby justifying the analysis of the combined dataset and highlighting shared patterns in AI literacy development across the two contexts. This consistency validates a common underlying mechanism for AI literacy development in these West African contexts. The study shows the importance of integrating technical AI skills with ethical principles, collaborative learning, and culturally appropriate strategies. Specifically, it offers actionable strategies for strengthening affective learning, designing collaborative behavioral interventions, embedding ethical reasoning into curricula, and contextualizing pedagogies for regional realities, thereby informing stakeholders on effective AI education in West Africa.